Evaluation of Antioxidant, Hypoglycemic and Hepatoprotective Effects of Leaf Extracts of Artemisia annua and Vernonia amygdalina in Alloxan Induced Diabetic Rats - Mabitine, Daniel Malo; Iheukwumere, Chidozie Charles; Gberikon, Grace Mwuese; Ogbonna, Innocent Okonkwo; Ogbonna, Chikezie Innocent Chuks; Ojobo, Omoche Adewa; Ado, Benjamin Vandelun; Okpe, Oche; Atabo, Samuel; Akogwu, Caleb Onoja; Itodo, Hanah N; Jacob, Mary; et al. (PSM Biological Research, 2025)
The global diabetes mellitus burdens and consequent combat approach has necessitated increased plant-based therapies. While non-fermented herbs and various synthetic drugs have been used, no sufficient success has been documented in the fight against this disease. The aqueous or non-fermented leaf extracts of Artemisia annua (A.AAQ) and Vernonia amygdalina (V.AAQ) and fermented leaf extracts of A. annua (A.AF) and V. amygdalina (V.AF) were evaluated for biochemical serum, lipid profile, in-vivo antioxidant parameters and body weight in alloxan induced diabetic rats. All extracts primarily V.AF and A.AF significantly decreased blood glucose levels (p<0.001). All extracts particularly A.AF, V.AF and A.AF+ V.AF significantly elevated Packed Cell Volume, Red Blood Cell Count, Hemoglobin Concentration, and Eosinophil levels (p<0.05; 0.001) but reduced Alanine phosphatase, Aspartate transaminase, Alkaline phosphatase and creatinine levels (p<0.001). Additionally, total cholesterol, Triglycerides and Low-density lipoprotein (LDL) were decreased (p<0.05; 0.01; 0.001), however, there was an increase in glutathione peroxidase (GPx) Protein, alongside a decrease in malondialdehyde (MDA) protein (p<0.001) in the diabetic rats. Body weights of diabetic rats significantly decreased (p<0.01; 0.001). In conclusion, the fermented extracts performed better in hypoglycemic activity in alloxan induced diabetic rats.